(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in an open field at AL-Sanowbar station of the Agricultural Scientific Research Center during 2022 spring, To study the effect of different levels of organic and mineral fertilization on the growth and productivity of potatoes (Cultiver Spunta) under the conditions of the coastal area, the study included seven treatments: (Control did not add any kind of organic or mineral fertilizers, 100% mineral fertilizers, 25% organic+75% mineral, 50% organic+50% mineral, 75% organic+25% mineral, 100% organic fertilizers, 100% organig+100% mineral). The results showed that the two fertilization treatments M100O100 and M75O25 were significantly superior to the rest of the treatments, in foliage area, leaf area index after 80 days of cultivation, which reached respectively 5823.46 and 5703.15m2 amounted to an increase of about 2198.91 and 2078.6m2 the control treatment, and leaf area index 2.50, 2.30 m2/m2respectively.As for productivity the treatment has outperformed M50O50 to the rest of the treatments, in terms of the average weight of the tuber and the average number of tubers per plant and average productivity per unit area where registered respectively 11733 g, 10 tuber/plant, 5045.89 kg/dunums, this treatment also achieved the best marketing production amounting to 4944.95 kg/dunums.